PERBEDAAN TANAMAN MELATI AIR (Echinodorus paleafolius) DAN KIAMBANG (Salvinia natans) SEBAGAI FITOREMEDIASI DALAM PROSES PENGOLAHAN LIMBAH CAIR LAUNDRY - Fitri Hidayah (JURNAL TECHLINK, 2020)
Laundry waste that is directly discharged into the environment can cause environmental pollution. Seeing this condition, of course it is necessary to strive for an environmental mitigation engineering system, so it is necessary to find an alternative treatment that is easy, inexpensive and effective in its application. The research aims to examine the ability of these aquatic plants to reduce phosphate, BOD, COD, TSS, temperature and pH content in laundry wastewater treatment using phytoremediation. The type of research used is experimental research that is to see the relationship between water jasmine and kiambang plants as phytoremediation in the process of laundry wastewater treatment. Data analysis using ANOVA analysis and different test. The results showed that there were significant differences in the parameters of BOD5, COD, TSS and Pospat (PO4) in water jasmine (Echinodorus paleafolius) and Kiambang (Salvinia natans) plants as phytoremediation in the laundry wastewater treatment process